Phosphorylated sodium alginate/APP/DPER intumescent flame retardant used for polypropylene. Issue 29 (28th March 2019) - Pallmann, Johanna; Ren, Yuan‐Lin; Mahltig, Boris; Huo, Tong‐Guo
ABSTRACT: Flame‐retardant polypropylene (FR‐PP) materials are realized by use of natural‐sourced flame‐retardant materials. Phosphorylated sodium alginate, ammonium polyphosphate, and dipentaerythritol are used to create an intumescent flame retardant (IFR). This realized flame retardant is embedded into polypropylene (PP) through melt blending method. The components, chemical structures, thermal properties, and degradation mechanisms of the samples are characterized by infrared spectrometry, thermogravimetric analysis, differential scanning calorimetry, scanning electron microscopy, and cone calorimeter test. The results indicate that an effective IFR is obtained due to gas phase and condensed phase synergistic flame‐retardant ability during combustion and degradation of FR‐PP. This work presents a facile method for preparing FR‐PP with efficient flame retardancy. This study is a first proof of concept for an innovative flame retardant, which could find application in future in the fields of automotive industry and the construction of electronic devices. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47794. Abstract :